A Novel Acinetobacter baumannii Bacteriophage Endolysin LysAB54 With High Antibacterial Activity Against Multiple Gram-Negative Microbes - Khan, Fazal Mehmood; Gondil, Vijay Singh; Li, Changchang; Jiang, Mengwei; Li, Junhua; Yu, Junping; Wei, Hongping; Yang, Hang (Frontiers in Cellular and Infection Microbiology, 2021)
The rapid spread and emergence of multidrug-resistant Acinetobacter baumannii and other pathogenic Gram-negative bacteria spurred scientists and clinicians to look for alternative therapeutic agents to conventional antibiotics. In the present study, an A. baumannii bacteriophage p54 was isolated and characterized. Morphological and genome analysis revealed that bacteriophage p54 belongs to Myoviridae family with a genome size of 165,813 bps. A novel endolysin, namely LysAB54, showing low similarity with other well-known related endolysins, was cloned, expressed, and characterized from the bacteriophage p54. LysAB54 showed significant bactericidal activity against multidrug-resistant A. baumannii and other Gram-negative bacteria, including Pseudomonas aeruginosa, Klebsiella pneumoniae, and Escherichia coli, in the absence of outer membrane permeabilizers. Based on all those observations, LysAB54 could represent a potential agent for the treatment of multidrug-resistant Gram-negative superbugs.